FIQH MAQASHID AL-KHITHAB: MUHAWALAT AL-'UTHUR 'ALA MAFHUM AL-MUSAWAH FI-SYAHADAT RAJUL WA-IMRAATAYN - Husni Mubarrak (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2020)
This article examines the problem of the diversity of interpretations of the testimony of two women equal to the testimony of one man in surah Al-Baqarah, verse 282. A number of interpretations that have surfaced use the hujjah, naqliy or aqliy, to reinforce the view that the testimony of two women is equal to one man. Some even return it to the verse of ta'abbudiy (unthinkable), so it does not open alternative interpretations because the verse is understood as final. By using the concept of "Fiqh Maqashid al-Khithab" as an ethical concept to understand the definition and meaning of the verses in a more equal, this article examines the discussions about the interpretation of the verses of "two women and one man".The result show that based on summarized from various treasures the book of commentaries on the Qur'an, classic and contemporary the intrepetation has various meaning about the concept of ta'abbudiy (unthinkable)This article examines the problem of the diversity of interpretations of the testimony of two women equal to the testimony of one man in surah Al-Baqarah, verse 282. A number of interpretations that have surfaced use the hujjah, naqliy or aqliy, to reinforce the view that the testimony of two women is equal to one man. Some even return it to the verse of ta'abbudiy (unthinkable), so it does not open alternative interpretations because the verse is understood as final. By using the concept of "Fiqh Maqashid al-Khithab" as an ethical concept to understand the definition and meaning of the verses in a more equal, this article examines the discussions about the interpretation of the verses of "two women and one man".The result show that based on summarized from various treasures the book of commentaries on the Qur'an, classic and contemporary the intrepetation has various meaning about the concept of ta'abbudiy (unthinkable).